Diffuse panbronchiolitis in an Asian immigrant. Issue 10 (October 1996) - Brugiere, O.; Milleron, B.; Antoine, M.; Carette, M. F.; Philippe, C.; Mayaud, C.
Abstract : Diffuse panbronchiolitis (DPB) is a disease with chronic inflammation exclusively located in the region of the respiratory bronchiole. It is largely restricted geographically to the Far East, and cases in Western countries are exceptional, even among Asian immigrants. A patient of Asian origin with DPB who had been living in France for 10 years is described. Only re-examination of the initial open lung biopsy specimen after an eight year period allowed this rare disease to be diagnosed correctly. The known efficacy of low dose erythromycin in DPB was again confirmed after failure of long term high dose corticosteroid therapy administered before an accurate diagnosis had been made.